Megalopolis unbound : - Pell, Claiborne (Praeger, 1966)
Sen. Pell was an early advocate of improved rail transport along the Northeast Corridor. In this volume he argues not only for revitalizing the existing passenger service and untangling choked highways and airways but also for exploring new technologies such as high-speed underground railroads powered by compressed air in pneumatic vacuum tubes. With black and white photo section. 233 pages with index.